Nekateri vidiki in prednosti treniranja juda za otroke in mladostnike - Šimenko, Jožef (Šport (Ljubljana), 2013)
The purpose of this article is to present some aspects and advantages of Judo training for children and adolescents. Judo is one of the safest forms of combat sports for young people. Children who train judo are gaining physical fitness, functional performance, self-confidence, determination, calmness, reliability, self-control, etc. They are also experiencing the strengthening of their social skills, making new friendships and personal growth. Judo is an excellent educational tool, which at several developmental levels, contributes to the child's biological and social development.
Keywords: adolescents; borilni športi; child; children; combat sports; judo; mladostniki; otroci; sport; šport